2016
DOI: 10.5812/jjm.39274
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and Genotypic Study of Inducible Clindamycin Resistance in Clinical Isolates of Staphylococcus aureus in Tabriz, Northwest Iran

Abstract: Background: Resistance to macrolide, lincosamide, and streptogramin B (MLSB) antibiotics is mediated by erm and msrA genes in Staphylococcus aureus. The expression of these genes can lead to three phenotypes, namely constitutive resistance (cMLSB), inducible resistance (iMLSB), which are resistant to macrolide, lincosamide, and streptogramin B antibiotics, and MSB phenotype, which is resistant only to macrolide and streptogramin B. Inducible clindamycin resistance is an important concern because it is not dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The prevalence of ermA/C was 13.1% ( n = 6) in our isolates. Nikbakht et al [34] showed the simultaneous presence of ermA and ermC in a significant number ( n = 39/215, 18.14%) of their isolates. Since strains with inducible resistance may mutate and alter to constitutive resistance, laboratories must correctly identify C susceptibility using the D-zone method for eliminating inducible C resistance.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of ermA/C was 13.1% ( n = 6) in our isolates. Nikbakht et al [34] showed the simultaneous presence of ermA and ermC in a significant number ( n = 39/215, 18.14%) of their isolates. Since strains with inducible resistance may mutate and alter to constitutive resistance, laboratories must correctly identify C susceptibility using the D-zone method for eliminating inducible C resistance.…”
Section: Discussionmentioning
confidence: 99%
“…A similar study in the Kashmir region showed that MRSA isolates were 100% resistant to penicillin, followed by erythromycin (78%) [11]. Also, studies from various parts of India [20,25,46,49] indicated similar antibiotic sensitivity patterns. Here, we detected 100% susceptibility to vancomycin; a similar study from the Kashmir region [50] found that S. aureus isolates were 100% susceptible to linezolid and vancomycin, followed by ciprofloxacin (60.43%).…”
Section: Discussionmentioning
confidence: 80%
“…32 The results of the antimicrobial susceptibility test by routine disk diffusion method showed that the highest antimicrobial resistance rate was against erythromycin 83.3% of S. aureus and clindamycin 53.3% of isolates, these results are close to those reported by previous studies. 29,33 In S. epidermidis, the resistance rates for erythromycin and clindamycin were 73.3 and 45%, respectively. These outcomes were lower than those reported by another study.…”
Section: Discussionmentioning
confidence: 99%
“…This result is lower than that reported in another study that showed a high rate of MRSA 93%. 34 Additionally, VRSA showed in 19 isolates (31.7%) of S. aureus 33 and among S. epidermidis isolates, 11.7% of isolates showed vancomycin resistance. This result is close from that reported by another local study that recorded a vancomycin resistance rate 10%, 32 but this result is far from this obtained by another local study that reported a resistance rate 40%.…”
Section: Discussionmentioning
confidence: 99%